The effect of the board composition on dividends: The case of Brazilian and Chilean family firms - Guadalupe del Carmen Briano-Turrent; Karen Watkins Fassler; Martha Luisa Puente-Esparza (European Journal of Family Business (EJFB), 2020)
Based on the agency theory, this paper analyzes whether family firms pay more dividends compared to no-family firms and identifies whether the board composition affects the dividend policy. Brazil and Chile have established mandatory dividends, retain lower cash holdings, pay higher dividends compared with other markets in the region. The sample of study is composed by 853 observations from 49 Brazilian and 32 Chilean top publicly listed firms in terms of market capitalization over the 11-year period from 2004 to 2014. Using an unbalanced panel data, results indicate that family controlled firms distribute more dividends and board composition namely; board size and the proportion of women on the board have a significant and positive impact on the dividend policy of the firm. By contrast, COB-CEO duality has a negative effect. Thus, dividend policy constitutes an effective corporate governance mechanism in mitigating the family' expropriation of minority shareholders' wealth.
Keywords: L20; O31; 650; Dividend policy; Family firms; Board composition; Latin America; Agency theory